Changes in serum NO, ET-1, and VEGF after cannulated screw fixation in patients with femoral neck fractures and their relationship with femoral head necrosis - Li, Ziqiang; Wang, Huanxi; Cao, Tingwei; Du, Kewei (Frontiers in Physiology, 2025)
BackgroundFemoral head necrosis (FHN) is one of the most serious complications in patients with femoral neck fractures (FNF) after cannulated screw fixation. Therefore, it is critical to predict the occurrence of FHN.MethodsFHN was diagnosed through clinical symptoms and imaging examinations. The serum levels of nitric oxide (NO), endothelin-1 (ET-1), and vascular endothelial growth factor (VEGF) in FNF patients were measured preoperatively and on postoperative days 3 and 5 using Enzyme-linked immunosorbent assay. The predictive value of NO, ET-1, and VEGF was evaluated using receiver operating characteristic curve analysis. The odds ratio (OR) for the risk factors of FHN was analyzed using multivariate logistic analysis.ResultThe serum levels of NO and VEGF decreased post-surgery in patients with FNF, with a more pronounced decrease in those who subsequently developed FHN, whereas patients who did not develop FHN showed no significant changes in these levels. Conversely, the serum level of ET-1 increased after surgery in FNF patients, with a marked rise in those who experienced FHN, while no significant change was observed in patients without FHN. ROC analysis indicated that serum levels of NO, ET-1, and VEGF have predictive value for FHN occurrence in FNF patients, with the highest predictive accuracy observed on day 5 post-surgery (Serum NO had the AUC (95% CI) of 0.74 (0.67–0.81), 0.70 (0.62–0.78) for ET-1 and 0.73 (0.65–0.80) for VEGF, p < 0.001 for all). Operation time after fracture ≥48 h, Garden classification of III and IV, Panwels classification of III, Serum ET-1 at 3 days post operation >75.24 pg/mL were independent risk factors for FHN occurrence but Serum NO at 3 days post operation >35.98 nmol/mL, Serum NO at 5 days post operation >33.62 nmol/mL, Serum VEGF at 5 days post operation >66.45 pg/mL were protective factors.ConclusionIn patients with FNF who developed FHN, serum levels of NO and VEGF were reduced, while ET-1 levels were elevated, compared to those who did not develop FHN. Furthermore, on day 5 post-surgery, these three markers provided the strongest predictive value for the occurrence of FHN in FNF patients.